TO ANALYZE THE SUPERSTİTİONS TRENDS OF PSYCHOLOGİCAL COUNSELİNG AND GUİDANCE DEPARTMENT STUDENTS - Nihat ÇALIŞKAN; Pınar İLTER (International Journal of Eurasia Social Sciences, 2016)
Superstitions steer people’s lives intentionally or involuntarily, affect their thoughts behaviors. Since individuals feel safer, they tend to believe in superstitions even if they change day by day for centuries. The main aim of this study is to find out the relationship between the superstition trends of psychological counseling and guidance department students and their grade levels and gender. The definition of superstition, psycho-social causes, functions are explained in the article. Also, the examples of the superstitions in Anatolia, in the western world, in Chinese society are included in the article. The sample of this study involves 260 students who has been studying at Psychological Counseling Guidance department at Ahi Evran University. A questionnaire involving the students’ demographic information, the existence of superstitions and the reasons was conducted. The results of this questionnaire were evaluated in charts. According to the findings of the study, there is a statically significant difference in favor of female students in terms of the level of having superstitions. As for the reasons of having a superstition, feeling psychologically relieved comes up as the main reason.